Pengembangan LKPD PAI Materi Peduli Lingkungan Berbasis Project Based Learning untuk Sustainability Awareness Siswa SD - Luqvan Edwin Maulana; Ospa Pea Yuanita Meishanti (Lembaga Yasin AlSys, 2026)
Students’ low sustainability awareness has become one of the problems in Islamic Religious Education (PAI) learning in elementary schools, particularly because environmental care material still tends to be oriented toward cognitive aspects and has not been optimal in shaping environmentally caring attitudes and behavior. This study aims to develop a PAI Student Worksheet (LKPD) on environmental care material based on Project Based Learning (PjBL) and to determine the level of feasibility and attractiveness of the product in supporting the improvement of sustainability awareness among sixth-grade students at SDN Sumbersari 2 Megaluh Jombang. This study used a Research and Development (R&D) method with the 4-D development model, which includes the stages of define, design, develop, and disseminate. The research subjects consisted of one material expert, one learning media expert, and 15 sixth-grade students. Data were collected through observation, interviews, expert validation sheets, and student response questionnaires, then analyzed descriptively using quantitative and qualitative approaches with percentages. The results of the study show that the developed LKPD obtained material expert validation of 90% in the highly feasible category and media expert validation of 81% in the highly feasible category. Students’ responses to the use of the LKPD obtained a percentage of 89.33% in the highly attractive category. The conclusion of the study affirms that the PAI LKPD on environmental care material based on PjBL is feasible for use as teaching material and has the potential to support the improvement of students’ sustainability awareness. The implications of this study indicate that project-based LKPD can serve as an innovative alternative teaching material that not only supports cognitive achievement but also encourages the formation of environmentally caring attitudes and behavior through active, contextual, and real-experience-based learning.